Description of Retail Prices for Food Products in the Markets of the Turkestan Territory in 60-80 XIX Century - Pustovaya Elena Sergeevna (International Journal on Integrated Education, 2022)
The article provides retail prices for basic products, such as: wheat, flour, barley, meat during the period of hostilities in Turkestan in 1860-1880.